Transabdominal preperitoneal laparoscopic approach for incarcerated inguinal hernia repair: A report of 73 cases. Issue 52 (December 2016) - Yang, Shuo; Zhang, Guangyong; Jin, Cuihong; Cao, Jinxin; Zhu, Yilin; Shen, Yingmo; Wang, Minggang
Abstract : Abstract: To investigate the efficacy, key technical points, and complication management of the transabdominal preperitoneal (TAPP) approach for incarcerated inguinal hernia repair. Seventy-three patients with incarcerated inguinal hernias underwent TAPP surgery in our department between Jan 2010 and Dec 2015. A retrospective review was performed by analyzing the perioperative data from these patients. The operation was successfully completed in all 73 patients. Operation time was 54.0 ± 18.8 minutes (range, 35–100 minutes). Length of stay was 3.9 ± 1.1 days (range, 3–9 days). There was 1 case of incisional infection, 32 cases of seroma, and 3 cases of postoperative pain during follow-up. All patients recovered after the appropriate treatment. No recurrence or fistula was observed. The TAPP approach represents a safe and effective technique for incarcerated inguinal hernia repair because of its potential in assessment of hernia content and decreasing incisional infection rate. However, it requires experienced surgeons to ensure safety with special attention paid to the key technical points as well as complication management.